INFLUENCE OF BOUNDARY CONDITIONS ON NONLINEAR RESPONSE OF LAMINATED COMPOSITE PLATES - Ćetković, Marina; Vuksanović, Đorđe (Journal of Applied Engineering Science, 2012)
In this paper the influence of different boundary conditions on geometrically nonlinear response of laminated composite plates is analyzed. Mathematical model, based on layer-wise displacement field of Reddy [1], is formulated using the von Karman, small strain large deflection theory. The principle if virtual displacements (PVD) is used to obtain the weak form of the problem. The weak form is discretized utilizing isoparametric finite element approximation. The originally coded MATLAB program is used to investigate the influence of different boundary conditions on geometrically nonlinear response of laminate composite plates. The accuracy of the numerical model is verified by comparison with the available results from the literature. Key words Geometrical nonlinearity, boundary conditions, composite plates, finite element
Keywords: plating; Lamins; finite element; composite plates; boundary conditions; Geometrical nonlinearity